Bridging the gaps between software engineering and Human-Computer Interaction. - Kazman, Rick (Software engineering notes.)
The First International Workshop on the Relationships between Software Engineering and Human-Computer Interaction was held on May 3--4, 2003 as part of the 2003 International Conference on Software Engineering, in Portland, OR, U.S.A. This workshop was motivated by a perception among researchers, practitioners, and educators that the fields of Human-Computer Interaction and Software Engineering were largely ignoring each other and that they needed to work together more closely and to understand each other better. This paper describes the motivation, goals, organization, and outputs of the workshop.